Educational Policy and the Australian Rural Economy - Perry Share; Geoffrey Lawrence; Colin Boylin (Journal of Research in Rural Education, 1994)
As in the past, the 1990s Australian economy continues to beshaped by external pressures: now,as part of theglobalisation ofinternational industry, trade, andfinance. Intensified by global recession, tradewars,and poor commodity prices, this process has contributed to a prolonged crisis in Australian agriculture and rural communities. TheAustralian government hasadopted policies ofrationalisation, deregulation, and privatisation in relationto bothrural industries and the provisionofeducationand training. The new educationand training agenda has implications for rural people. While government policy for education in rural areas in the past has included both genericand targetted policy initiatives, thesehave recently converged: "Rural" policies increasingly reflect the new agenda. The new approach may not fully benefit rural people, however, as it is based on urban models that may neglect the specific needs and constraints of rural areas.